0573 Slow Wave Sleep Is Associated With An Increased Prevalence Of Hypertension In Patients With Obstructive Sleep Apnea. (27th April 2018) - Ren, R; Zhang, Y; Yang, L; Zhou, J; Tan, L; Li, T; Li, X; Tang, X
Abstract: Introduction: Majority of obstructive sleep apnea (OSA) patients exhibit OSA events associated interrupt sleep (e.g., decreased slow wave sleep (SWS) and rapid eye movement (REM) sleep, increased N1 and N2 sleep). There are variations in the activity of autonomic nervous systems across different sleep stages, which may lead to the fluctuation of blood pressure (BP). In particular, an increased vagal tone and reduced sympathetic tone could result in lower BP during SWS. We intended to examine whether different amounts of sleep stages, especially SWS, modifies the relationship between OSA and prevalent hypertension in a large number of OSA patients, and in separate male and female patients. Methods: A total of 7107 patients with apnea-hypopnea index (AHI) ≥ 5/h were recruited into this study (84.7% males, mean age = 45.34 ± 11.78 years). Hypertension was defined based either on direct blood pressure measures or on physician diagnosis. Multivariable logistic regression models were adjusted for age, gender, body mass index (BMI), Epworth sleep scale, tobacco use, alcohol use, AHI, nocturnal oxygen desaturation, arousal index, sleep duration and efficiency. Results: A 53.8% was found to have hypertension in total observed OSA patients. In the multi-adjusted model and based on SWS percentage, OSA in quartiles 1 (<0.4%; OR 1.45, 95% CI 1.13–1.70, p=0.001) and 2 (0.4–5.8%; OR 1.21, 95% CI 1.04–1.61, p=0.03), but not quartile 3, had significantly greater odds of prevalent hypertension compared to that in quartile 4 (>12.3%). A significant effect modification by gender on the SWS-hypertension association was found (p=0.004), such association was only existed in male, not in female. No any significant relationship between hypertension and other three sleep stages (N1, N2 and REM %) were obtained in total patients and in separated male and female groups. Conclusion: Decreased SWS, not changes in N1, N2 and REM sleep, is associated with increased odds of prevalent hypertension in male OSA patients. Support (If Any): This work was supported by the National Natural Science Foundation of China (81530002, 81770087).